Evaluasi Peraturan Daerah Nomor 10 Tahun 2009 Tentang Penyelenggaraan dan Retribusi Pelayanan Pemakaman Jenazah di TPU Bergota Kota Semarang Tahun 2014-2016 - manisah .; Kushandajani .; Lusia Astrika (Journal of Politic and Government Studies, 2017)
ABSTRACTBurial ground is one of social needs that should be fulfilled by theGovernment of Semarang City. They have provided a public burial ground inKelurahan Randusari called TPU.Bergota which has 30 hA in large, but thecondition of TPU.Begota today is getting narrow (overload). The operation ofburial ground’s setup in Semarang refers to Government Local RegulationNumber 10 of 2009 about Operation and Retribution of Burial in Semarang City.The method of this research is qualitative approach with observation andinterview as the method of collecting data. The informan in this research is theHead of Gardening Department of Housing and Residential Area of SemarangCity, the Head of Gardening and Funeral Section, officers of UPTD region IV,and people of Kelurahan Randusari and Meteseh.The result shows that the operation of Government Local RegulationNumber 10 of 2009 about Operation and Retribution of Burial Services inSemarang has not yet operated well. It can be proven by the condition of the placethat shows amount of gravestone that being a house, inappropriate size of thegravestone, no grass planted on the funeral, and not well organized.The recommendation for the Government of Semarang is they had betterhold an open socialization for all of Semarang society and do a revision ofGovernment Local Regulation according to the condition right now.Keywords: Burial Ground, Evaluation, Semarang